Mãe e bebê prematuro extremo: possibilidade de vínculo em situação adversa - Rios, Iamara Jacintho de Azevedo (2007)
This study examines the relationship between mothers and premature babies, during prolonged hospitalization in a neonatal intensive therapy unit (NITU). To consider the matter, an interview with the mother of an extreme premature baby was conducted. She recorded the hospitalization period using a scrapbook, i.e., a book through which hospitalization history is recorded in details, using customized pages and a wide variety of materials. The history of both mother and baby, here called Maria and Matheus, allowed us to explain the importance of the consideration by the speech pathologist/audiologist of such relationship in a hospital setting, having as main reference the aspects of the Winnicottian theory. The study approached particularly the concepts of primary mother concerns and holding, which are fundamental in the first moments of life, defined by the author as absolute dependency. Finally, the study concludes that, even in such an adverse situation as is baby's prolonged hospitalization, the mother is indeed able to develop her own mother style. Therefore, the entire team of professionals involved, including the speech pathologist/audiologist, is responsible for helping increase the offer of holding in an environment different from home; this certainly supports the development of healthy children, who are able to pass to the next stages of growth